Synthesis, characterization, photophysical and electrochemical properties of a new non - planar perylene diimide with electron donating substituent - Mostafanejad, S. Melika; Bodapati, Jagadeesh B.; Ozkar, Saim; Icil, Huriye (Elsevier, 2018)
A new nonplanar and soluble, donor-acceptor-donor system (3) based on a perylene diimide chromophore (1) consisting on 5-amino-4-cyano-3-methylthiophene-2-carboxamide (2) as electron donating unit at imide position has been synthesized. The photophysical and electrochemical properties were systematically investigated in different solvents. All the results of structural characterization reveal that the thiophene units are not coplanar with the core of perylene diimide. Spectroscopic properties of 3 in solution show variations with the organic solvent used. In the polar aprotic and strongly electron donating solvents, such as DMF, DMAC and NMP, 3 exhibits intense absorption features in the UV-visible absorption spectrum covering the wavelength range of 300-800 nm with excellent absorptivity. Photoinduced electronic excitation energy transfer was noticed in polar aprotic solvents from electron donating substituent to the perylene core. The non-planar geometry of 3 prevented efficient energy transfer between donor and acceptor.
Keywords: Thiophene; Perylene diimide; Non - planarity; Donor - acceptor; Electron transfer; Excellent thermal and electrochemical stability